Paranormal - Tony Oursler vs Gustavo Rol - Oursler, Tony 1957-; Rol, Gustavo Adolfo 1903-1994 (M. Corraini, 2017)
Paranormal. Tony Oursler vs Gustavo Rol' is the catalogue of the exhibition hosted from November 3, 2017 at Pinacoteca Agnelli, which continues its research path on the theme of collecting. This time the topic is the paranormal: a collection of works by American artist Tony Oursler and his personal objects collection about the occult world, dialogue with works by psychic painter Gustavo Rol. The selection has been made by Oursler himself together with the curator Paolo Colombo and the director of the Pinacoteca Marcella Pralormo. 00Exhibition: Pinacoteca Agnelli, Turin, Italy (23.11.2017-25.02.2018)
Catalog of an exhibition held at the Pinacoteca Giovanni e Marella Agnelli, Turin, Italy, Nov 3, 2017-Feb. 25, 2018
Keywords: Ausstellungskatalog